Biochemical, Pharmacological, and Structural Characterization of New Basic PLA2 Bbil-TX from Bothriopsis bilineata Snake Venom. (30th September 2012) - Corasolla Carregari, Victor; Stuani Floriano, Rafael; Rodrigues-Simioni, Lea; Winck, Flavia V.; Baldasso, Paulo Aparecido; Ponce-Soto, Luis Alberto; Marangoni, Sergio
Abstract : Bbil-TX, a PLA2, was purified from Bothriopsis bilineata snake venom after only one chromatographic step using RP-HPLC on μ -Bondapak C-18 column. A molecular mass of 14243.8 Da was confirmed by Q-Tof Ultima API ESI/MS (TOF MS mode) mass spectrometry. The partial protein sequence obtained was then submitted to BLASTp, with the search restricted to PLA2 from snakes and shows high identity values when compared to other PLA2 s. PLA2 activity was presented in the presence of a synthetic substrate and showed a minimum sigmoidal behavior, reaching its maximal activity at pH 8.0 and 25–37 ∘ C. Maximum PLA2 activity required Ca 2+ and in the presence of Cd 2+, Zn 2+, Mn 2+, and Mg 2+ it was reduced in the presence or absence of Ca 2+ . Crotapotin from Crotalus durissus cascavella rattlesnake venom and antihemorrhagic factor DA2-II from Didelphis albiventris opossum sera under optimal conditions significantly inhibit the enzymatic activity. Bbil-TX induces myonecrosis in mice. The fraction does not show a significant cytotoxic activity in myotubes and myoblasts (C2C12). The inflammatory events induced in the serum of mice by Bbil-TX isolated from Bothriopsis bilineata snake venom were investigated. An increase in vascular permeability and in the levels of TNF-a, IL-6, and IL-1 was was induced. Since Bbil-TX exerts a stronger proinflammatory effect, the phospholipid hydrolysis may be relevant for these phenomena.